How gambling problems relate to health and wellbeing in Australian households: Evidence from the Household Income and Labour Dynamics of Australia Survey - Tulloch, Catherine; Hing, Nerilee; Browne, Matthew; Rockloff, Matthew (My University, 2023)
Gambling harms can impact the health and wellbeing of both individuals who gamble and those close to them. While harms occur across a spectrum of gambling risk levels, most research is conducted on people close to those gamblers who have severe problems. This study examined the health and wellbeing of people living with gamblers across the entire spectrum of gambling risk levels, via secondary analysis of the nationally- representative Household Income and Labour Dynamics in Australia Survey (HILDA). The subsample of inter- est comprised 13,698 respondents without a gambling problem of their own, aged between 15 and 84, and who lived in households where all residents completed the Problem Gambling Severity Index (PGSI). Health and wellbeing were measured via the SF-6D, the SF-36, and subjective wellbeing measures. Compared to those living in non-problem gambling households, participants living in problem-gambling households reported significantly lower mean SF-6D scores, lower scores on the SF-36 mental health domain, and significantly less satisfaction with both their financial situation and with feeling part of their local community. Participants living in moderate- risk gambling households also reported less satisfaction with their financial situation than those in non-problem gambling households. Conclusions: The results indicate that measurable impacts to the health and wellbeing of those living with gamblers occur predominantly at the more severe end of the risk level spectrum, except for financial dissatisfaction, which is also evident in those residing with gamblers categorised as moderate-risk.
Addictive Behaviors
Keywords: Health and wellbeing